1998
DOI: 10.1097/00005344-199802000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Concentrations of 17β-Estradiol Inhibit the Synthesis of Nitric Oxide Synthase in Macrophages Via a Receptor-Mediated System

Abstract: We investigated the effect of estrogen on inducible nitric oxide synthase (iNOS), which is not well understood, in contrast to the known effect of estrogen on endothelial nitric oxide synthase (eNOS). When J774 cells, a murine macrophage cell line, were incubated with interferon-gamma and lipopolysaccharide, iNOS was induced, and a large amount of NO was released. Pre- or coincubation with 17beta-estradiol inhibited this induction of iNOS protein and NO release; however, 17beta-estradiol did not have a direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
44
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 29 publications
6
44
1
1
Order By: Relevance
“…In fact, using ER␣-and ER␤-null microglia and receptor antagonists, we demonstrate that ER␣ is necessary for E 2 inhibition of NF-B. These data are consistent with previous reports which showed that the reactivity of macrophages, known to express endogenous ERs, is strongly regulated by E 2 (6,17,43,44) and that ER␣ is necessary for the anti-inflammatory activity of E 2 in inflammatory pathologies (1,10,14,31,42). By showing that ER␣ mediates the inhibition of NF-B transport, we thus provide the mechanism to explain this receptor-specific anti-inflammatory activity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, using ER␣-and ER␤-null microglia and receptor antagonists, we demonstrate that ER␣ is necessary for E 2 inhibition of NF-B. These data are consistent with previous reports which showed that the reactivity of macrophages, known to express endogenous ERs, is strongly regulated by E 2 (6,17,43,44) and that ER␣ is necessary for the anti-inflammatory activity of E 2 in inflammatory pathologies (1,10,14,31,42). By showing that ER␣ mediates the inhibition of NF-B transport, we thus provide the mechanism to explain this receptor-specific anti-inflammatory activity.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, other inflammatory pathological conditions, such as wound healing (1), atherosclerosis (for a review, see reference 18), ischemia (10), uveitis (28), and leukodystrophy (27), were shown to be influenced by E 2 , which decreased disease susceptibility, severity, and damage. In support of this in vivo evidence, results obtained from cell culture studies have shown that E 2 down-regulates the expression of inflammatory genes, such as those coding for the inducible form of nitric oxide synthase (iNOS) or matrix metalloprotease 9, enzymes directly involved in the progression of the inflammatory response, and inhibits the biochemical and morphological activation of macrophages (6,17,43). Thus, evidence accumulated so far is uniformly concordant in identifying estradiol as a protective agent against the induction of the inflammatory response.…”
mentioning
confidence: 92%
“…A number of studies have suggested that estrogen modifies macrophage function and the production of inflammatory mediators (16,26,39,55). However, we found an increase in disease severity score and histological scores in both op/ϩ and op/op mice with DSS colitis treated with 17␤-estradiol compared with mice with DSS colitis treated with placebo.…”
Section: Discussioncontrasting
confidence: 64%
“…Numerous studies have examined the actions of 17␤-estradiol on macrophages. Such studies confirm a mechanistic role for high-affinity estrogen receptors, but yield conflicting reports as to the effects of 17␤-estradiol on cell function, ranging from inhibition to promotion of activation (compare, for example, findings reported by Hayashi et al, 1998;Lu et al, 2004;Vegeto et al, 2004;Sakazaki et al, 2005). On the other hand, little attention has been given to the effects of 17␤-estradiol metabolites, such as 2MEO, on macrophage function.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen receptor-␤ agonists have attracted attention as potential anti-inflammatory agents (Koehler et al, 2005). Previous studies in LPS/IFN␥-stimulated J774 cells found in one case modest suppression of nitric-oxide production by 17␤-estradiol (Hayashi et al, 1998) and in another case enhancement (Sakazaki et al, 2005), but did not examine other inflammatory mediators. However, in the present study concentrations of 17␤-estradiol far greater than those required to saturate high-affinity estrogen receptors had no effect on J774 macrophage activation.…”
mentioning
confidence: 99%